Inverter fuzzy speed control of multi-machine system series-connected fed by a single five-phase an asymmetrical 19-level inverter with less number of switches - Bessaad, T.; Benbouali, A.; Khelifi Otmane, K.; Taleb, R.; Sahraoui, H.; Iqbal, A. (Національний технічний університет "Харківський політехнічний інститут", 2025)
5-phase permanent magnet synchronous machines (PMSMs) are widely used in modern electric drive systems due to their superior torque density, improved fault tolerance, and reduced torque ripple. These characteristics make them ideal for demanding applications such as electric vehicles, aerospace systems, and industrial automation. Problem. Despite their advantages, conventional multimachine systems using multilevel inverters and PI controllers suffer from sensitivity to parameter variations, high torque ripple, and increased cost and complexity due to the large number of power switches. The goal of this work is to design and validate a compact robust drive system that enables independent vector control of two series-connected 5-phase PMSMs using a reduced switch count asymmetrical 19-level inverter and fuzzy logic controllers. Methodology. The proposed system is modeled in the phase domain and transformed using Clarke and Park transformations to enable decoupled control. Mamdani-type fuzzy logic controllers are implemented for both speed and current regulation. The system is simulated in MATLAB/Simulink to evaluate performance under dynamic conditions and parameter variations. Results. The fuzzy logic controller significantly outperforms the conventional PI controller, achieving a settling time of 0.06 s versus 0.15 s, a steady-state speed error of 0.4 % compared to 1.9 %, and a torque ripple reduction of 47 %. Under robustness testing with doubled inertia, the fuzzy controller maintains stable and accurate control, whereas the PI controller fails. Additionally, the inverter achieves near-sinusoidal output with a total harmonic distortion of less than 4.5 %, and the switch count is reduced by 66 % compared to traditional 36-switch designs. Scientific novelty. This work presents the first implementation of independent vector control for two seriesconnected PMSMs using a single 12-switch asymmetrical 19-level inverter and model-free fuzzy logic control, offering a simpler and more efficient alternative to existing approaches.

П’ятифазні синхронні машини з постійними магнітами (PMSMs) широко використовуються в сучасних системах електроприводу завдяки високій щільності і зменшеній пульсації крутного моменту, та підвищеній відмовостійкості. Ці характеристики роблять їх ідеальними для багатьох застосувань – електромобілі, аерокосмічні системи та промислова автоматика. Проблема. Незважаючи на переваги, традиційні багатомашинні системи, що використовують багаторівневі інвертори та ПІ-регулятори, є чутливими до змін параметрів, високої пульсації крутного моменту, а також високій вартості і складності через велику кількість силових ключів. Метою роботи є розробка та валідація компактної надійної системи приводу, яка забезпечує незалежне векторне керування двома послідовно з’єднаними п’ятифазними PMSM з використанням асиметричного 19-рівневого інвертора зі зменшеною кількістю ключів та нечітких логічних контролерів. Методологія. Запропонована система моделюється у фазовій області з використанням перетворень Кларка та Парка для забезпечення розв’язаного керування. Реалізовано нечіткі логічні контролери типу Мамдані для регулювання швидкості і струму. Система моделюється в MATLAB/Simulink для оцінки продуктивності в динамічних умовах та зміни параметрів. Результати. Нечіткий логічний регулятор значно перевершує традиційний ПІ-регулятор, досягаючи часу встановлення 0,06 с проти 0,15 с, помилки швидкості 0,4 % проти 1,9 % і зниження пульсацій крутного моменту на 47 %. При випробуванні на надійність з подвоєним моментом інерції нечіткий логічний регулятор підтримує стабільне та точне керування, тоді як ПІ-регулятор виходить з ладу. Крім того, інвертор досягає майже синусоїдального вихідного сигналу із загальним коефіцієнтом гармонічних спотворень менше 4,5 %, а кількість перемикачів скорочено на 66 % порівняно з традиційними конструкціями з 36 перемикачами. Наукова новизна. У роботі представлена перша реалізація незалежного векторного управління для двох послідовно з’єднаних PMSMs з використанням одного асиметричного 19-рівневого інвертора з 12 перемикачами та нечіткого логічного управління без моделі, що пропонує більш просту та ефективну альтернативу існуючим підходам.
Keywords: multi-machine system; fuzzy logic controller; independent vector control; asymmetric inverter; багатомашинна система; контролер нечіткої логіки; незалежне векторне керування; асиметричний інвертор